Method for preparing lithium-rich manganese-based positive electrode material through pressurized oxygen enrichment
By adopting high-temperature refiring treatment with pressurized oxygen-rich environment in the lithium-rich manganese-based cathode material, the problem of oxygen release and structural instability of the material at high voltage is solved, and its electrochemical performance and cycle life are significantly improved.
Patent Information
- Application Number
- CN202411829591.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-29
AI Technical Summary
Lithium-rich manganese-based positive electrode materials have poor electrochemical performance at high voltages, limiting their commercial applications.
The pressurized oxygen-rich environment is used to perform durocination of lithium-rich manganese-based positive electrode material at high temperature, and oxygen elements are introduced to enhance the oxygen anion reaction and improve the structural stability of the material.
It significantly improves the first-time Coulomb efficiency, cycle stability and rate performance of the material, extends the cycle life of the battery, and improves the retention rate of voltage and capacity.
Smart Images

Figure CN119898825A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium-ion batteries, and in particular relates to a method for preparing a lithium-rich manganese-based positive electrode material by pressurizing oxygen-enrichment. Background Art
[0002] With the increasing depletion of non-renewable energy and the continuous increase of ecological environmental pollution, the development of clean energy has become the focus of global attention. Among the many clean energy technologies, electrochemical energy storage and conversion devices have attracted much attention due to their high efficiency and environmental protection. As a representative of electrochemical energy storage and conversion devices, lithium-ion batteries (LIBs) have broad application prospects. They are mainly composed of four parts: positive electrode, negative electrode, electrolyte and separator. The positive electrode material is the main lithium ion (Li + ) donor, which has an important impact on the capacity and cost of lithium-ion batteries.
[0003] Lithium-rich manganese-based cathode materials have the general formula xLi2MnO3·(1-x)LiMO2, where M is a transition metal such as Ni, Co, or Mn. This type of material is considered a strong candidate for the next generation of high energy density cathode materials due to its high discharge capacity (about 280 mAh / g), high average voltage (3.6 volts), excellent mass specific energy density (over 1000 Wh / kg), low cost, and simple synthesis and preparation process. However, lithium-rich manganese-based cathode materials also have some problems that need to be solved, such as low first coulombic efficiency, continuous attenuation of capacity and voltage during the cycle, and poor rate performance. These problems mainly stem from the release of oxygen from the material at high voltage and the transformation of the layered to spinel phase, which limits its commercial application.
[0004] At present, the surface coating technology is mainly used to improve the electrochemical performance of lithium-rich manganese-based positive electrode materials. The materials are coated with aluminum oxide, aluminum fluoride, silicon dioxide, aluminum phosphide and other substances to inhibit the release of oxygen and protect the electrodes from the corrosion of the electrolyte. This improves the performance of the material to a certain extent, but the modification method is complicated, costly and inefficient, which limits its wide application.
[0005] Therefore, developing a simple, efficient, and environmentally friendly method to comprehensively improve the electrochemical performance of layered Li-rich manganese cathodes is crucial for their commercial application in high-energy-density batteries. Summary of the invention
[0006] The technical problem to be solved by the present invention is a method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment, which is simple in process, environmentally friendly, and has excellent first coulombic efficiency, continuous retention rate of capacity and voltage during the cycle, and rate performance.
[0007] The technical solution of the present invention is: A method for preparing a lithium-rich manganese-based positive electrode material by pressurizing oxygen-enriched materials, the specific steps of which are as follows: Step 1: Prepare precursor solution: Dissolve a lithium source, a nickel source, a cobalt source, a manganese source, and a complexing agent in water, mix them evenly, and obtain a precursor solution; Step 2: Spray drying: spray drying the precursor solution to obtain a precursor powder; Step 3: High temperature sintering: The precursor powder is sintered at high temperature in an air atmosphere to obtain a lithium-rich manganese-based layered oxide; Step 4: Preparation of lithium-rich manganese-based positive electrode materials Put a lithium-rich manganese-based layered oxide into a high-pressure reactor, turn on the circulating cooling water, introduce oxygen until the pressure of the high-pressure reactor is 0.5MPa-10MPa, increase the temperature, and carry out oxygen-enriched reaction in an oxygen environment for 30 minutes under the conditions of the reactor temperature of 600℃-800℃ and the pressure of 0.5MPa-10MPa, cool to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material.
[0008] In step 4, the reactor temperature is 600°C and the pressure is 0.5MPa-10MPa.
[0009] The molar ratio of the lithium source, the nickel source, the cobalt source and the manganese source is 1.9:0.2:0.2:0.8.
[0010] The lithium source is lithium acetate, the nickel source is nickel acetate, the cobalt source is cobalt acetate, and the manganese source is manganese acetate.
[0011] The concentration of the lithium source in the precursor solution is 0.38 mol / L.
[0012] The complexing agent is citric acid, and the concentration of the complexing agent in the precursor solution is 0.3 mol / L.
[0013] During spray drying, the peristaltic pump feed rate is 200-1000 mL / h, the spray drying inlet temperature is 230° C., the outlet temperature is 115° C., the needle passing frequency is 15 Hz, the spray pressure is 0.2 MPa, and the spray drying atmosphere is air.
[0014] During high temperature sintering, the heating rate is 3°C / min, and the calcination is performed at 1000°C for 20 min in an air atmosphere.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention introduces oxygen elements into the lithium-rich manganese-based positive electrode material by means of a pressurized oxygen-rich environment, so that more oxygen can participate in the oxygen anion reaction, thereby increasing the amount of oxygen participating in the reaction. This improvement increases the valence state of the transition metal, thereby increasing the initial discharge capacity. At the same time, it stabilizes the MO chemical bonds of active transition metals such as Ni, Co, and Mn (M), effectively hinders the precipitation of lattice oxygen under high voltage, significantly improves the structural stability of the material, and thereby improves the cycle stability of the lithium-rich manganese-based positive electrode material. In addition, the present invention can also reduce the release of irreversible surface oxygen of part of the lithium-rich manganese positive electrode material, thereby improving the initial coulombic efficiency (ICE).
[0016] (2) The present invention improves the internal structural stability of the lithium-rich manganese-based positive electrode material by heating and pressurizing the re-firing treatment, and embeds oxygen into the lithium-rich manganese layered structure. This treatment process not only significantly improves the internal structural stability of the material, but also improves the first-cycle coulomb efficiency and cycle stability of the battery. Moreover, the prepared lithium-rich manganese-based positive electrode material has a first-cycle capacity of up to 289mAh / g at a voltage of 4.8V, a first-cycle efficiency of up to 87.73%, and a 100-cycle capacity retention rate of 79.19%, which greatly improves the first coulomb efficiency, cycle performance, and voltage and capacity attenuation of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The first cycle charge and discharge curves of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention at 0.1C; Figure 2 The graph is a graph of the electrochemical cycle discharge capacity of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention at 1C; Figure 3 The graph is a graph of the median voltage of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention under electrochemical cycle conditions of 1C; Figure 4 It is a scanning electron microscope image of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention; Figure 5 It is the XRD diagram of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-4 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0018] Example 1 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The mixture was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based hierarchical oxide (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2); 4) Preparation of lithium-rich manganese-based positive electrode materials Weigh 10g of lithium-rich manganese-based layered oxide and spread it flat in the body of a high-pressure reactor. Set the heating temperature of the reactor to 600°C for 30min and the pressure to 0.5MPa. Start the circulating cooling water, introduce oxygen into the high-pressure reactor to make the pressure of the reactor 0.5MPa, increase the temperature until the temperature of the high-pressure reactor reaches the specified temperature of 600°C, and react at a pressure of 0.5MPa and a temperature of 600°C for 30min. Then cool the reactor to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material (recorded as 0.5MPa-600°C / 30min).
[0019] The lithium-rich manganese positive electrode material, conductive agent (SuperP) and binder (sodium carboxymethyl cellulose CMC) prepared in Example 1 were mixed into a slurry at a mass ratio of 85:10:5, and coated on an aluminum foil current collector after stirring to obtain a lithium-rich manganese-based positive electrode plate; the lithium-rich manganese-based positive electrode plate was assembled into a 2025 button battery in an argon-filled glove box with an oxygen and water content of less than 0.01ppm, and a charge and discharge test was performed on the Xinwei test system: It uses metal Li sheet as reference electrode and counter electrode, Celgard-2400 diaphragm, LiPF6 (1mol / L) / EC+DEC+EMC (solvent volume ratio is 1:1:1) as electrolyte, and battery activation condition is 50℃ / 24h. The test voltage window is 2.0~4.8V, the test temperature is 27±1℃, the first three cycles are activated at 0.1C rate (1C=200mAh / g), and the 1C rate cycle is used from the 4th cycle. The electrochemical performance test results are shown in Table 1, and the electrochemical first cycle charge and discharge curve at 0.1C is shown in the figure below. Figure 1 As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown.
[0020] Example 2 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The mixture was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based hierarchical oxide (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2); 4) Preparation of lithium-rich manganese-based positive electrode materials Weigh 10 g of lithium-rich manganese-based layered oxide and spread it flat in the body of a high-pressure reactor. Set the heating temperature of the reactor to 600°C for 30 min and the pressure to 5.0 MPa. Start the circulating cooling water, introduce oxygen into the high-pressure reactor to make the pressure of the reactor 5.0 MPa, increase the temperature until the temperature of the high-pressure reactor reaches the specified temperature of 600°C, and react at a pressure of 5.0 MPa and a temperature of 600°C for 30 min. Then cool the reactor to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material (recorded as 5.0 MPa-600°C / 30 min).
[0021] A lithium-rich manganese-based positive electrode sheet was prepared to assemble a 2025 button cell. The charge and discharge test was carried out on the Xinwei test system in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1. The electrochemical first cycle charge and discharge curve at 0.1C is shown in Figure 1 As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown.
[0022] Example 3 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The mixture was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based hierarchical oxide (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2); 4) Preparation of lithium-rich manganese-based positive electrode materials Weigh 10 g of lithium-rich manganese-based layered oxide and spread it flat in the body of a high-pressure reactor. Set the heating temperature of the reactor to 800°C for 30 min and the pressure to 5.0 MPa. Start the circulating cooling water, introduce oxygen into the high-pressure reactor to make the pressure of the reactor 5.0 MPa, increase the temperature until the temperature of the high-pressure reactor reaches the specified temperature of 800°C, and react at a pressure of 5.0 MPa and a temperature of 800°C for 30 min. Then cool the reactor to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material (recorded as 5.0 MPa-800°C / 30 min).
[0023] A lithium-rich manganese-based positive electrode sheet was prepared to assemble a 2025 button cell. The charge and discharge test was carried out on the Xinwei test system in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1. The electrochemical first cycle charge and discharge curve at 0.1C is shown in Figure 1 As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown.
[0024] Example 4 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The mixture was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based hierarchical oxide (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2); 4) Preparation of lithium-rich manganese-based positive electrode materials Weigh 10 g of lithium-rich manganese-based layered oxide and spread it flat in the body of a high-pressure reactor. Set the heating temperature of the reactor to 600°C for 30 min and the pressure to 10 MPa. Start the circulating cooling water, introduce oxygen into the high-pressure reactor to make the pressure of the reactor 10 MPa, increase the temperature until the temperature of the high-pressure reactor reaches the specified temperature of 600°C, and react at a pressure of 10 MPa and a temperature of 600°C for 30 min. Then cool the reactor to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material (recorded as 10 MPa-600°C / 30 min). A lithium-rich manganese-based positive electrode sheet was prepared to assemble a 2025 button cell. The charge and discharge test was carried out on the Xinwei test system in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1. The electrochemical first cycle charge and discharge curve at 0.1C is shown in Figure 1 As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown.
[0025] Comparative Example 1 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor material powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The material was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based cathode material (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2) was used as the standard sample.
[0026] A lithium-rich manganese-based positive electrode sheet was prepared to assemble a 2025 button cell. The charge and discharge test was carried out on the Xinwei test system in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1. The electrochemical first cycle charge and discharge curve at 0.1C is shown in Figure 1As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown.
[0027] Comparative Example 2 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The mixture was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based hierarchical oxide (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2); 4) Preparation of lithium-rich manganese-based positive electrode materials Weigh 10 g of lithium-rich manganese-based layered oxide and spread it flat in the body of a high-pressure reactor. Set the heating temperature of the reactor to 600°C for 30 min and the pressure to 0.2 MPa. Start the circulating cooling water, introduce oxygen into the high-pressure reactor to make the pressure of the reactor 0.2 MPa, increase the temperature until the temperature of the high-pressure reactor reaches the specified temperature of 600°C, react at a pressure of 0.2 MPa and a temperature of 600°C for 30 min, then cool the reactor to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material (recorded as 0.2 MPa-600°C / 30 min).
[0028] A lithium-rich manganese-based positive electrode sheet was prepared to assemble a 2025 button cell. The charge and discharge test was carried out on the Xinwei test system in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1. The electrochemical first cycle charge and discharge curve at 0.1C is shown in Figure 1 As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown.
[0029] Comparative Example 3 1) Preparation of acetate-citric acid precursor solution Weigh 94.6 g of lithium acetate dihydrate, 24.3 g of nickel acetate tetrahydrate, 24.3 g of cobalt acetate tetrahydrate and 99.3 g of manganese acetate tetrahydrate, dissolve in 5 L of deionized water, mix well, add 315 g of citric acid monohydrate as a complexing agent, stir with a magnetic stirrer for 1 hour, mix the solution well, and obtain an acetate-citric acid precursor solution; 2) Preparation of precursor material powder The acetate-citric acid precursor solution was pumped into a spray dryer for spray drying, the spray drying inlet air temperature was 230°C, the outlet air temperature was 115°C, the peristaltic pump speed was controlled at 600-800mL / h, the needle passing frequency was 15Hz, and the spray pressure was 0.2MPa to obtain a precursor material powder; 3) Preparation of lithium-rich manganese-based layered oxides The precursor powder was placed in a crucible and calcined in a muffle furnace. Fresh air was continuously introduced into the muffle furnace during the calcination process. The temperature was raised to 1000°C at a heating rate of 3°C / min. The mixture was calcined at 1000°C for 20 minutes. After cooling in the furnace, a lithium-rich manganese-based hierarchical oxide (0.5Li2MnO3·0.5Li(Ni 0.33 Co 0.33 Mn 0.33 )O2); 4) Preparation of lithium-rich manganese-based positive electrode materials Weigh 10 g of lithium-rich manganese-based layered oxide and spread it flat in the body of a high-pressure reactor. Set the heating temperature of the reactor to 1000°C for 30 min and the pressure to 10 MPa. Start the circulating cooling water, introduce oxygen into the high-pressure reactor to make the pressure of the reactor 10 MPa, increase the temperature until the temperature of the high-pressure reactor reaches the specified temperature of 1000°C, react at a pressure of 10 MPa and a temperature of 1000°C for 30 min, then cool the reactor to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material (recorded as 10 MPa-1000°C / 30 min).
[0030] A lithium-rich manganese-based positive electrode sheet was prepared to assemble a 2025 button cell. The charge and discharge test was carried out on the Xinwei test system in the same manner as in Example 1. The electrochemical performance test results are shown in Table 1. The electrochemical first cycle charge and discharge curve at 0.1C is shown in Figure 1 As shown, the electrochemical cycle discharge capacity curve at 1C is as follows Figure 2 As shown, the median voltage curve of the electrochemical cycle at 1C is as follows Figure 3 shown. from Figure 1 It can be seen that the materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 all meet the requirements of 0.5Li2MnO3·0.5Li(Ni0.33 Co 0.33 Mn 0.33 )O2 has a typical two-stage charging curve. There is a short platform below 4.5V, where the redox reaction of transition metal cations mainly occurs; there is a long platform below 4.5V, where the redox reaction of oxygen anions mainly occurs. The materials re-fired under different heating and pressurization conditions have different platform lengths at 4.5V. Specifically, the platforms of all re-fired samples are slightly longer than those of the standard samples. This is because the pressurized oxygen-rich environment allows more oxygen to participate in the oxygen anion reaction, increasing the amount of oxygen participating in the anion reaction. When the oxygen pressure is 5Mpa, the first discharge capacity of the battery produced by treating the lithium-rich manganese-based positive electrode material at 600℃ / 30min can reach up to 289.83mAh / g. Figure 2 It can be seen that the capacity of the lithium-rich manganese-based positive electrode material treated at 600°C / 30min with an oxygen pressure of 5Mpa has almost no decay after 100 cycles.
[0031] Table 1 As can be seen from Table 1, from Examples 1 to 4, the first discharge capacity of the battery prepared by treating the lithium-rich manganese-based positive electrode material with the pressurized oxygen-rich re-firing pressure of 5 MPa at 600°C / 30 min can reach up to 289.83 mAh / g, and the first Coulomb effect is as high as 87.73%.
[0032] By comparing Examples 1, 2, 4 and Comparative Example 2, it can be seen that in the preparation process of the lithium-rich manganese-based positive electrode material treated with pressurized oxygen-enriched re-firing according to the present invention, under the same conditions of 600°C / 30min, the lithium-rich manganese-based positive electrode material treated with an oxygen pressure of 5.0MPa is used to prepare a battery, and its first-cycle discharge capacity is 289.83mAh / g and the first-cycle coulomb efficiency is 87.73%, which are both higher than the standard sample comparative example 1 (267.39mAh / g-77.72%) without pressurized oxygen-enriched treatment, and the experimental results of comparative example 2 at the same temperature and time: 0.2MPa (267.62mAh / g-81%), 0.5MPa (285.5mAh / g-78.03%) and 10MPa (280.32mAh / g-83.4%). The oxygen pressure of the present invention is 5.0 MPa, and the temperature is 600° C. / 30 min to treat the lithium-rich manganese-based positive electrode material, which has the best effect of improving the structural stability and electrochemical performance of the lithium-rich layered oxide.
[0033] From the comparison of Examples 2, 3, 4 and Comparative Examples 2 and 3, it can be seen that in the process of preparing the lithium-rich manganese-based positive electrode material by pressurized oxygen-rich re-firing treatment described in the present invention, the structural stability of its lithium-rich layered oxide will be improved under an oxygen pressure of 5.0 MPa and a temperature of 600°C / 30min, and the first cycle capacity and capacity retention rate of the battery will be improved. If the temperature is too high at 1000°C / 30min, it will be counterproductive. Under an oxygen pressure of 5.0 MPa and a temperature of 800°C / 30min, the first cycle capacity of the battery is 280.32 mAh / g and the capacity retention rate is 77.95%, and the electrochemical performance is lower than that of Example 2; at a temperature of 1000°C / 30min, the capacity is directly reduced to 248.21 mAh / g, and the capacity retention rate is only 63.79%. Therefore, pressure and temperature are crucial to the battery performance of the material, and only when the conditions are appropriate will it be beneficial to improve the initial discharge capacity and coulomb efficiency.
[0034] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a lithium-rich manganese-based positive electrode material by pressurized oxygen enrichment, characterized in that: The following steps are involved: Step 1: Prepare precursor solution: Dissolve a lithium source, a nickel source, a cobalt source, a manganese source, and a complexing agent in water, mix well, and obtain a precursor solution; Step 2: Spray drying: spray drying the precursor solution to obtain a precursor powder; Step 3: High temperature sintering: The precursor powder is sintered at high temperature in an air atmosphere to obtain a lithium-rich manganese-based layered oxide; Step 4: Preparation of lithium-rich manganese-based positive electrode materials Put a lithium-rich manganese-based layered oxide into a high-pressure reactor, turn on the circulating cooling water, introduce oxygen until the pressure of the high-pressure reactor is 0.5MPa-10MPa, increase the temperature, and carry out oxygen-enriched reaction in an oxygen environment for 30 minutes under the conditions of the reactor temperature of 600℃-800℃ and the pressure of 0.5MPa-10MPa, cool to room temperature, turn off the circulating cooling water, and obtain a lithium-rich manganese-based positive electrode material.
2. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: In step 4, the reactor temperature is 600°C and the pressure is 0.5MPa-10MPa.
3. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: The molar ratio of the lithium source, the nickel source, the cobalt source and the manganese source is 1.9:0.2:0.2:0.
8.
4. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: The lithium source is lithium acetate, the nickel source is nickel acetate, the cobalt source is cobalt acetate, and the manganese source is manganese acetate.
5. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: The concentration of the lithium source in the precursor solution is 0.38 mol / L.
6. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: The complexing agent is citric acid, and the concentration of the complexing agent in the precursor solution is 0.3 mol / L.
7. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: During spray drying, the peristaltic pump feed rate is 200-1000 mL / h, the spray drying inlet temperature is 230° C., the outlet temperature is 115° C., the needle passing frequency is 15 Hz, the spray pressure is 0.2 MPa, and the spray drying atmosphere is air.
8. The method for preparing lithium-rich manganese-based positive electrode materials by pressurized oxygen enrichment according to claim 1, characterized in that: During high temperature sintering, the heating rate is 3°C / min, and the calcination is performed at 1000°C for 20 min in an air atmosphere.